Analisis Aspek Pemasaran pada Bisnis Bengkel Las Bersaudara Bagan Batu - Nasution, Nurul Fadhilah (Maliki Interdisciplinary Journal, 2025)
This research discusses the market and marketing aspects of the Bengkel Las Bersaudara business. The purpose of this study is to determine the feasibility of market and marketing aspects of the Brothers Welding Workshop business. The research method used is a qualitative method by means of observation. The results in this study indicate that the Bersaudara Welding Workshop is feasible in its market and marketing aspects.This study discusses the market and marketing aspects of the Bersaudara Welding Workshop business. The purpose of this study was to determine the feasibility of market and marketing aspects of the Bersaudara Welding Workshop business. The research method used is a qualitative method by means of observation. The results of this study indicate that the Bersaudara Welding Workshop is feasible in its market and marketing aspects. This business also offers innovative, high quality products and competitive prices and customers can pay a down payment first when ordering products. This strategy can attract customers' interest in buying products and can attract customers to come back to buy. In this research, the results of the analysis carried out at the Brothers Welding Workshop in assessing market and marketing aspects obtained a total score of 21/5 with an average score of 4.2, so the business is feasible. This is because the feasibility level in a business feasibility study is >3 then it can be said to be feasible.